2008
DOI: 10.4257/oeco.2008.1202.05
|View full text |Cite
|
Sign up to set email alerts
|

Subtidal benthic marine algae of the Todos os Santos Bay, Bahia State, Brazil

Abstract: The Todos os Santos bay is a Brazilian coastal marine area that was appointed as top priority for biological conservation. However, there are still too few studies about the local composition of marine communities. The aim of the present investigation was to survey the diversity of marine algae in the sub-tidal zone around the reefs of the Todos os Santos bay. Samples from seven different sites in the bay were obtained by scuba diving through qualitative and quantitative methods, being the collections repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 15 publications
2
10
0
15
Order By: Relevance
“…Similar results to this study were obtained in other surveys of subtidal flora performed by Yoneshigue-Valentin et al (2006) for the REVIZEE Program for benthic diversity of the Brazilian continental shelf, as well by Marins et al (2008) for Todos os Santos Bay, in the state of Bahia. In these studies, the Ceramiales, Dictyotales and Bryopsidales orders were the most abundant.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar results to this study were obtained in other surveys of subtidal flora performed by Yoneshigue-Valentin et al (2006) for the REVIZEE Program for benthic diversity of the Brazilian continental shelf, as well by Marins et al (2008) for Todos os Santos Bay, in the state of Bahia. In these studies, the Ceramiales, Dictyotales and Bryopsidales orders were the most abundant.…”
Section: Discussionsupporting
confidence: 81%
“…More recent investigations have been conducted into the phycological flora of the subtidal region of Gaibu Beach on the coast of Pernambuco (Pereira et al 2007 b), Arvoredo Island in Santa Catarina , Todos os Santos Bay in Bahia (Marins et al 2008), Cabo Frio island in Rio de Janeiro (Villaça et al 2008), the setentrional coast of the Bacia do Potiguar in Rio Grande do Norte (Cocentino et al 2010) and on Santo Aleixo Island in Pernambuco (Carvalho et al 2013). Studies have also been undertaken involving the rhodoliths beds found along the Brazilian coast (Riul et al 2009, Amado-Filho et al 2010, and Francini-Filho et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Relationship between fish communities and environmental variables Subtidal benthic communities on rocky shores are likely to have a less diverse algae community in the Todos os Santos bay (MARINS et al, 2008). In the present study, turf algae cover was the dominant benthic organism by far.…”
Section: Discussionmentioning
confidence: 72%
“…Sargassum beds constitute an important link between benthic primary producers and several levels of consumers (DUBIASKI-SILVA;MASUNARI, 2008;JACOBUCCI et al, 2009). The abundance of brown algae in the benthic communities, mainly Sargassum, suggests that the rocky shores of the study area had not been subjected to organic pollution (CECERE et al, 1991;BERCHEZ;OLIVEIRA, 1992;FURNARI, 1999;COLEMAN et al, 2008;MARINS et al, 2008).…”
Section: Discussionmentioning
confidence: 99%